RECLAIMING VOICES: RED INTERSECTIONALITY AND SUBALTERN COUNTERPUBLICS IN INDIGENOUS TIKTOK TRENDS ‘SAVAGE DAUGHTER’ - Emanuelle, Glory (Pengkajian Amerika, Universitas Gadjah Mada, 2026)
Popular culture often misrepresents Native American people by portraying them through a colonial lens; thus, Indigenous people of the northern part of America are mostly perceived by the caricature of their own culture or ultimately effaced from the media. In particular, Native American women are experiencing double marginalization. The colonial lens that put their people is mostly built on a patriarchal system, which is not only detrimental to the Indigenous’s existence but also almost effectively erases their women’s identity. Social media platforms such as TikTok have enabled marginalized groups to express themselves and regain their identities. This research employs Natalie Clark’s Red Intersectionality and Nancy Fraser’s Subaltern Counterpublics to analyze selected TikTok videos from the trend “Savage Daughter” by Sarah Hester Ross’ cover, which numerous Indigenous women creators use to show their pride and culture. This study suggests that Native American women are, in fact, not erased from the media representation, but also provides critical insight into how digital platforms empower marginalized groups to resist dominant ideologies.